Amending or Terminating Conservation Easements: The New Hampshire Experience (Utah Environmental Law Review; Vol 33 No 1 (2013), 2014)
The New Hampshire legislature enacted laws permitting the establishment of conservation easements in 1973. Since that time, thousands of acres in the State have been preserved and protected from development through the efforts of government entities and the land trust community, the latter of which is comprised of nonprofit land conservation organizations recognized as tax exempt under the Internal Revenue Code. As of October 2013, the National Conservation Easement Database had gathered data on 3,500 individual conservation easements in New Hampshire held by land trusts, the State, the federal government, and local municipalities.